The Influence Of Harvest Labor Productivity Factors On Palm Oil Production At PTPN VI Business Unit Batang Hari - Sophia Sophia (Fakultas Pertanian Universitas Muara Bungo, 2022)
This study aims to determine the labor productivity of oil palm harvesters at PTPN VI Batang Hari Business Unit, and to determine the effect of age, years of service, education level, salary and premiums as well as motivation in the productivity of harvesters at PTPN VI Batang Hari Business Unit. This research was conducted at PT Perkebunan Nusantara VI, Batang Hari Business Unit, which is located in Muhajirin Village, Jambi Outer City District, Muaro Jambi Regency. The research will be carried out from March 16 to March 27, 2021. This study was conducted to analyze the effect of labor productivity factors on harvesters on oil palm production at PTPN VI Batang Hari Business Unit. The data collection method used was direct interviews with list of questions (questionnaire) and secondary data collection from the company. The analytical method used is descriptive quantitative analysis and multiple linear regression analysis (F test and T test). The results showed (1) the productivity of harvesters at PTPN VI Batang Hari Business Unit as a whole from the samples taken, the results were more than one hundred percent. (2) together the factors of labor productivity of harvesters affect oil palm production in PTPN VI Batang Hari Business Unit. While in a single test the factors that affect the productivity of harvesters are the Salary and Premiums, and Motivation factors.Keywords: Plantation; Productivity; and Labor